2012
DOI: 10.1007/s00270-012-0529-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Intraductal Radiofrequency Ablation is a Safe Treatment for Malignant Biliary Obstruction: Feasibility and Early Results

Abstract: In this group of patients, it appears that this new approach is feasible and safe. Efficacy remains to be proven in future, randomized, prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 10 publications
2
43
0
1
Order By: Relevance
“…RFA has been widely used in the ablation of esophagus dysplasia [8], rectum cancer [9], and liver carcinoma [10]. As for intraluminal radiofrequency ablation, there is limited clinical experience and a small quantity of reports [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RFA has been widely used in the ablation of esophagus dysplasia [8], rectum cancer [9], and liver carcinoma [10]. As for intraluminal radiofrequency ablation, there is limited clinical experience and a small quantity of reports [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have looked into the feasibility and safety of this procedure [2][3][4]. The present study retrospectively analyzed 47 patients who underwent 65 consecutive percutaneous intraluminal RFA combined with biliary stenting for the treatment of extrahepatic obstructive jaundice between September 2011 and May 2014.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports of the use of intraductal RFA for the treatment of unresectable malignant biliary obstructions with percutaneous and endoscopic approaches, demonstrating its feasibility and safety; pain, cholangitis and asymptomatic biochemical pancreatitis have been reported as the only common complications (2,6,13), while hepatic coma, newly diagnosed left bundle branch block and partial liver infarction have been reported as uncommon complications (2,14,15). However, a few cases of hemobilia and mortality following intrabiliary RFA have also been reported (15).…”
Section: A B C D F E Discussionmentioning
confidence: 99%
“…et al 46 indicated that percutaneous intraductal radiofrequency ablation combined with biliary stenting was feasible and safe for malignant biliary obstruction including cholangiocarcinoma.…”
Section: 44mentioning
confidence: 99%